2021
DOI: 10.2214/ajr.20.24636
|View full text |Cite
|
Sign up to set email alerts
|

Use of Enteric Contrast Material for Abdominopelvic CT in Penetrating Traumatic Injury in Adults: Comparison of Diagnostic Accuracy Systematic Review and Meta-Analysis

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Other concerns include the risk of aspiration, especially in patients who will proceed to laparotomy [ 4 , 21 ]. In addition, recent studies found that triple-contrast CT has a sensitivity equal to that of single-contrast CT in detecting HVI and that the addition of enteric contrast did not provide any diagnostic benefit [ 4 , 14 , 15 ]. As a result, most trauma centres, including the unit at CMJAH, have adopted single-contrast CT as the standard modality [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other concerns include the risk of aspiration, especially in patients who will proceed to laparotomy [ 4 , 21 ]. In addition, recent studies found that triple-contrast CT has a sensitivity equal to that of single-contrast CT in detecting HVI and that the addition of enteric contrast did not provide any diagnostic benefit [ 4 , 14 , 15 ]. As a result, most trauma centres, including the unit at CMJAH, have adopted single-contrast CT as the standard modality [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that there is no diagnostic benefit in the addition of enteric contrast for detecting HVI compared to an IV contrast-only CT. In the trauma setting, single-contrast CT is often performed, as triple-contrast CT results in delayed diagnosis and surgical intervention due to the time required for enteric opacification [ 4 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enteric (oral and/or rectal) contrast media are currently not recommended for the first CT in blunt abdominal trauma and are not routinely used in penetrating trauma. The results of a recent meta-analysis [ 19 ] did not support the use of enteric contrast media in penetrating trauma, and this position has been endorsed by the World Society of Emergency Surgery (WSES) [ 1 ], which cited the lack of improved accuracy, delayed examination time, increased cost, and potential surgical delay due to aspiration risk. However, local experience, surgeon preference, and new evidence [ 20 ] keep the debate open and the topic undecided.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…1 A meta-analysis of 12 studies and 1287 subjects found that enteric contrast adds no additional diagnostic benefit when compared with the use of IV contrast material alone. 2 A study on a single emergency department's visits between the years of 2004 and 2014 found that CT with IV contrast alone had a sensitivity of 88% and specificity of 72% in detecting bowel injuries in the setting of penetrating abdominopelvic trauma, while past studies on CT with IV, oral and rectal contrast have shown sensitivities of 67-100% and specificities of 80-97%. 3 While the utility of rectal contrast alone lacks substantial research, Thorisdottir et al found that CT with gastrointestinal contrast had similar sensitivity as CT with IV contrast only, based on analysis of over 600 patients with penetrating abdominal trauma.…”
mentioning
confidence: 99%